A thermostable GH8 endoglucanase of Enterobacter sp. R1 is suitable for β- glucan deconstruction - Ontañon, Ornella Mailen; Ghio, Silvina; Marrero Diaz De Villegas, Rubén; Garrido, Mercedes Maria; Talia, Paola Mónica; Fehér, Csaba; Campos, Eleonora (Elsevier, 2020)
Glycoside hydrolase family 8 (GH8) includes endoglucanases, lichenases, chitosanases and xylanases, which are essential for polysaccharides breakdown. In this work, we studied a thermally stable GH8 from the cellulose synthase complex of Enterobacter sp. R1, for deconstruction of β-glucans. The biochemical characterization of the recombinant GH8ErCel showed high specificity towards barley β-glucan and lichenan and lower activity on carboxymethylcellulose and swollen cellulose, yielding different length oligosaccharides. By molecular modeling, six conserved subsites for glucose binding and some possible determinants for its lack of xylanase and chitosanase activity were identified. GH8ErCel was active at a broad range of pH and temperature and presented remarkable stability at 60 °C. Additionally, it hydrolyzed β-glucan from oat and wheat brans mainly to tri- and tetraoligosaccharides. Therefore, GH8ErCel may be a good candidate for enzymatic deconstruction of β-glucans at high temperature in food and feed industries, including the production of prebiotics and functional foods.